A Rare Associated Anomaly in Tetralogy of Fallot: Scimitar Syndrome in an Infant - Çınar,Betül (2021)
Abstract Pulmonary venous connections may be infrequently abnormal in patients with tetralogy of Fallot (TOF). A special subgroup of partial anomalous pulmonary venous return,"scimitar cyndrome", and its coexistence with TOF is less frequently reported. It may proceed unnoticed, as cyanosis already predominates in the clinical picture. This uncommon association must be kept in mind for patients with TOF who have an accessory flow in the inferior vena cava, especially when all pulmonary venous return to the left atrium is not clearly seen.